PERAN AUDIT INTERNAL DAN KOMITMEN MANAJEMEN DALAM PENERAPAN GOOD CORPORATE GOVERNANCE - Ketut Tanti Kustina; Devy Leviyanthie Zulianto (Universitas Pendidikan Nasional, 2017)
The purpose of this study to determine the extent to which the role of internal audit and management commitment in the implementation of Good Corporate Governance at the Denpasar Branch Office PT Bank QNB Indonesia Tbk. This research is research with descriptive qualitative method. Data collection techniques were conducted with interviews, and documentation studies. The results show that Good Corporate Governance is the underlying philosophy of corporate management based on GCG principles. Internal audit is a GCG tool in order for the bank to have compliance with all regulations at the office of Bank QNB denominational branch. The implementation is done periodically by the Internal Audit Unit and daily by internal control. The results are in the form of recommendations resulting from internal audits in improving the corporate governance process on risk, control, and performance management of the Bank Indonesia QNB company's organization. The role of management commitment is realized with the integrity of leadership in the implementation of Good Corporate Governance as defined in the vision, mission, organizational structure, standards and procedures and business activities of banks by all levels of bank organization, and such soft-structure of Bank QNB in implementing GCG.Keywords: Good Corporate Governance, Internal Audit, Management Commitment.